Homestay, Sleepover, and Commensality: Three Intimate Methods in the Study of “Mixed” Families - Asuncion Fresnoza-Flot (Genealogy, 2022)
Scholars most often adopt qualitative data-gathering methods, notably interviews, to access the lifeworld of “mixed” families. Nonetheless, when research questions require vivid details about their lives, other data-collection techniques may be needed. “Intimate” research methods, characterised by proximate contacts and interactions with “mixed” couples and their families, appear particularly useful in this regard. Drawing from ethnographic studies of mixed families of Filipino and Thai migrant women in Belgium and The Netherlands, the present paper unveils the heuristic value of three intimate methods—homestays, sleepovers, and commensality—in perceiving the realities of these women’s couple and family lives. Homestays and sleepovers allow an in-depth understanding of ways of life within homes, interpersonal interactions, and their intricacies. Commensality (i.e., eating together) offers “snapshots” of the lives of mixed families, providing insights complementary to other methods such as interviews. Hence, the three intimate methods explored in this paper are social sites in which one can view details, otherwise invisible or unspoken, of the lives of mixed families, ranging from power dynamics to intergenerational relations, from the family’s social class status and cross-border social ties to emotional situations.